Equitable Allocations in Northern Fisheries: Bridging the Divide for Labrador Inuit - Kourantidou, Melina; Hoagland, Porter; Dale, Aaron; Bailey, Megan (Frontiers in Marine Science, 2021)
Canada has undertaken commitments to recognize the rights of Indigenous Peoples in fisheries through policies and agreements, including Integrated Fishery Management Plans, the Reconciliation Strategy, and Land Claim Agreements. In addition to recognizing rights, these commitments were intended to respect geographic adjacency principles, to enhance the economic viability of Indigenous communities, and to be reflective of community dependence on marine resources. We examined the determinants of quota allocations in commercial fisheries involving Nunatsiavut, Northern Labrador, the first self-governing region for the Inuit peoples in Canada. It has been argued that current fishery allocations for Nunatsiavut Inuit have not satisfied federal commitments to recognize Indigenous rights. Indicators that measure equity in commercial allocations for the turbot or Greenland halibut (Reinhardtius hippoglossoides) and northern shrimp (Pandalus borealis) fisheries were identified and assessed. In these two cases, historical allocations continue to predominate over allocations based upon equity or other social or economic considerations. We illustrate equity-enhancing changes in the quota distribution under scenarios of different levels of inequality aversion, and we make qualitative assessments of the effects of these allocations to Nunatsiavut for socioeconomic welfare. This approach could benefit fisheries governance in Northern Labrador, where federal commitments to equity objectives continue to be endorsed but have not yet been integrated fully into quota allocations.